2018
DOI: 10.3892/ol.2018.8658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of PVP and PKP in the treatment of OVCFs after bilateral resection of ovarian cancer

Abstract: The clinical efficacy of percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) in the treatment of osteoporotic vertebral compression fractures after bilateral resection of ovarian cancer was investigated. Eighty-six patients with osteoporotic vertebral compression fractures after bilateral resection of ovarian cancer admitted to the Second People's Hospital of Hefei from September, 2015 to August, 2016 were selected and randomly divided into control group (n=43) and observation group (n=43). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The reason that we only tested the efficacy of Tirobot in the later is that the procedures in this surgery, like pinpointing entry point of the needle, should be performed with high-precision biopsy and can be resolved by a robot. Besides, between the two modes of vertebroplasty, PKP has higher safety and better prognosis than percutaneous vertebroplasty (PVP) [ 27 29 ]. In clinical practice, PVP needs less time.…”
Section: Discussionmentioning
confidence: 99%
“…The reason that we only tested the efficacy of Tirobot in the later is that the procedures in this surgery, like pinpointing entry point of the needle, should be performed with high-precision biopsy and can be resolved by a robot. Besides, between the two modes of vertebroplasty, PKP has higher safety and better prognosis than percutaneous vertebroplasty (PVP) [ 27 29 ]. In clinical practice, PVP needs less time.…”
Section: Discussionmentioning
confidence: 99%
“…The reason that we only tested the e cacy of Tirobot in the later is that the procedures in this surgery, like pinpointing entry point of the needle, should be performed with high precision in biopsy and can be resolved by a robot. Besides, between the two modes of vertebroplasty, PKP has higher safety and better prognosis than percutaneous vertebroplasty (PVP) [29][30][31]. In clinical practice, PVP needs less time.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the risk factors of type-B, type-C, and type-S leakage were reported, respectively. Bone cement dispersion-type is diffuse, which is a risk factor for types B and S. Most scholars focus on the relationship between bone cement morphology and recurrent fracture after the operation of injured vertebrae [ 21 ]. However, there are a lack of reports on the relationship between bone cement morphology and bone cement leakage [ 22 ].…”
Section: Discussmentioning
confidence: 99%